The impact of road infrastructure development on ecosystems and communities - Kuncoro, Edi; Wurarah, Rully Novie; Erari, Ishak E (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: Road infrastructure is essential for economic growth and improving connectivity between regions. This study looks at how environmental, social, and financial communities are affected by the development of the Arfai-Pami road infrastructure in Manokwari Selatan District, Manokwari Regency. Methods: This research uses qualitative and quantitative methods with the philosophy of positivism. Data were collected in several places in the Arfai and Pami areas, including South Manokwari, through observation, interviews, and document analysis. Result: The results showed that road construction improved accessibility and local economic growth, with an increase in the value of social variables by 0.365 and economic variables by 0.759, respectively. However, apparent consequences include a 33.87% decrease in forest area, a decrease in green space, an increased likelihood of flash flooding downstream due to land use change, and a decrease in infiltration surface area. In addition, road construction causes pollution, habitat disruption, and changes in water flow patterns, which can lead to erosion. Changes in the lifestyle and employment of local people is one of the significant social impacts. Residents benefit from increased employment opportunities, while others face increased living costs and loss of agricultural land. Relocation or compensation is a frequent social issue. The conclusion of this study emphasizes how important it is to balance ecosystem preservation and road infrastructure development. Especially in Arfai-Pami, road infrastructure development should be done holistically considering environmental, social, and economic impacts. Conclussion: To maximize benefits and reduce adverse effects, communities, government, and industry players need to be involved in the planning and implementation of road infrastructure projects.